Aplikasi Teknologi Fermentasi Limbah Kubis sebagai Pengawet Alami Penanganan Pasca Panen Ikan pada Kelompok Nelayan di Tempat Pelelangan Ikan (TPI) Purnama Dumai - Yuni Fatisa; Lisa Utami (Universitas Mathla'ul Anwar Banten, 2021)
APPLICATION OF CABBAGE WASTE FERMENTATION TECHNOLOGY AS A NATURAL PRESERVATIVE IN POST-HARVEST HANDLING OF FISH IN FISHER GROUPS AT FISH AUCTION PLACE OF PURNAMA DUMAI. One of the solutions that can be used to preserve fish naturally economically and efficiently is to use cabbage waste. Cabbage (Brassica oleracea) is a well-known vegetable, widely produced, easy to obtain and cheap in price. The use of cabbage waste as a natural preservative for fresh fish is used to naturally preserve fish so that the misuse of preservatives that are harmful to the human body is no longer used.